Psychometric properties of the Brazilian version of the Factors Influencing Adherence to Standard Precautions Scale - Gabriela da Cunha Januário; Vanderlei José Haas; Damiana Aparecida Trindade Monteiro; Elucir Gir; Fernanda Maria Vieira Pereira Ávila; Mariana Alvina dos Santos; Stephane Bouchoucha; Silmara Elaine Malaguti Toffano (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To evaluate the psychometric properties of the Brazilian version of the Factors Influencing Adherence to Standard Precautions Scale. Method: Psychometric study, conducted in a hospital in Minas Gerais, with 407 nursing professionals. Data collection took place between August 2022 and September 2023 using a sociodemographic questionnaire and the Brazilian version of the scale. To characterize the sample, measures of central tendency and dispersion were used. Regarding the psychometric properties of the instrument, validity evidence methods based on the internal structure were adopted, using confirmatory factor analysis and reliability, through test-retest and internal consistency. Results: The confirmatory factor analysis revealed a model that was adequately fit to the dimensional structure. The domains showed factor loadings ranging from 0.31 to 0.73 for leadership, 0.345 to 0.83 for justification, 0.12 to 0.69 for organizational culture and practice, 0.37 to 0.84 for contextual cues, and 0.52 to 0.80 for judgment. Regarding reliability, good correlation was observed for the instrument's domains, with an intraclass correlation range (0.48 to 0.95) and internal consistency (0.52 to 0.80). Conclusion: The Brazilian version of the scale revealed a model adjusted to the dimensional structure proposed by the Australian authors, proving to be valid, stable and reliable to identify the factors that influence adherence to standard precautions among nursing professionals.